PENGARUH PENILAIAN KESEHATAN BANK TERHADAP KINERJA KEUANGAN BANK SYARIAH DI INDONESIA - Welly, Welly; Hari, Kurnia Krisna (Balance : Jurnal Akuntansi dan Bisnis, 2018)
This study aims to provide empirical evidence about the effect of bank soundness by using Risk Profile, Good Corporate Governance, Earnings, Capital (RGEC) methods on the financial performance of sharia commercial banks in Indonesia. The formulation of the problem in this research is whether there is an effect of the soundness of the Islamic Commercial Bank with the RGEC method with the banking performance in Indonesia in the 2011-2015 period? How much influence does the bank's health level have on the RGEC method on the performance of Islamic Banks in Indonesia? The research sample consisted of 7 Islamic banks in Indonesia. The data used are quarterly financial statements of sharia commercial banks and GCG implementation reports. The statistical method used to test the research hypothesis is multiple linear regression. The results of data testing stated that there was no heterocedasticity, autocorrelation, multicollinearity, and data with normal distribution. The results showed that Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Net Operating Margin (NOM) and Capital Adequacy Ratio (CAR) had an influence on the financial performance of Islamic commercial banks, while Good Corporate Governance (GCG) did not have influence on the financial performance of Islamic commercial banks. The effect of bank soundness on the financial performance of Islamic banks was 39.40%, while 60.60% was influenced by other factors outside this study.